En busca de nosotros mismos: Acerca de la necesidad de la sabiduría para el hombre de hoy (2005)
In the middle of a society that constantly invites us to be absent and distant, it seems relevant to ask, by means of a reflexive and interiorized attitude, if a way to find ourselves would be to stop the dehumanizing process that is depriving men of his essential human qualities, in western civilizations.